Children and the changing family : between transformation and negotiation - Jensen, An-Magritt; McKee, Lorna (RoutledgeFalmer, 2003)
This timely and thought-provoking book explores how social and family change are colouring the experience of childhood.
Keywords: Children -- Social conditions.; Children -- Family relationships.; Work and family.; Children of divorced parents.; Social change.; Social Change; Enfants -- Conditions sociales.; Enfants -- Relations familiales.; Travail et familles.; Enfants de divorcés.; Changement social.; Enfance -- Relations familiales.; SOCIAL SCIENCE -- Children's Studies.; Children -- Family relationships; Children of divorced parents; Children -- Social conditions; Social change; Work and family; Kinderen.; Gezinsrelaties.; Sociale verandering.; Chômage.; Enfant.; Enfant du divorce.; Famille.; Relation familiale.; Travail.; Electronic books.